Islamic Education Innovation Through Instagram: Efforts to Build Islamic Character in Students in Higher Education - Chaerunnisa, Chaerunnisa; Dahlia, Dahlia; Erinda, Dheva; Hastuty, Ade (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
This research is motivated by the challenges of shaping Islamic character among university students in the digital era, where social media platforms such as Instagram significantly influence young people’s behavior and religious values. The main problem of this study lies in the limited innovation of Islamic education that utilizes digital platforms effectively to instill religiosity and moral values. The purpose of this study is to analyze the innovation of using Instagram as a learning and digital da’wah medium to strengthen Islamic character among university students. The research applies a qualitative approach with a literature study method, reviewing various studies and practices of Islamic education through social media. The results show that Instagram can serve as an effective medium to reinforce Islamic values through educational content such as Qur’anic quotes, short videos, infographics, and lecturer-student collaborations. The use of digital media is proven to enhance students’ understanding of moral values, active participation, and religious awareness when applied strategically and with educational orientation. This innovation aligns with the principles of student-centered learning and contextual education, positioning social media not only as entertainment but as a creative and relevant learning space for developing students’ Islamic character.